Manuscritos y epigrafía latina. Notas de lectura sobre CIL 2, 2637 y 5082 - Rabanal Alonso, Manuel Abilio; González Alonso, E. (Estudios humanísticos. Geografía, historia y arte, 1996)
Different Latin inscriptions are contained in a unpusblished manuscript. This document, wich autor is unknown, has been dated about 1540, and is kept in the Library of Real Academia de la Historia, Madrid (mark 9 / 6120). Hübner's corpus CIL 2, 2637 and CIL 2, 5082 inscriptions appear in this document in a way that show us they are a same piece.